Afferent Loop Syndrome after Roux-en-Y Total Gastrectomy Caused by Volvulus of the Roux-Limb - Hideki Katagiri; Kana Tahara; Kentaro Yoshikawa; Alan Kawarai Lefor; Tadao Kubota; Ken Mizokami (Case Reports in Surgery)
Afferent loop syndrome is a rare complication of gastric surgery. An obstruction of the afferent limb can present in various ways. A 73-year-old man presented with one day of persistent abdominal pain, gradually radiating to the back. He had a history of total gastrectomy with a Roux-en-Y reconstruction. Abdominal computed tomography scan revealed dilation of the duodenum and small intestine in the left upper quadrant. Exploratory laparotomy showed volvulus of the biliopancreatic limb that caused afferent loop syndrome. In this patient, the 50 cm long limb was the cause of volvulus. It is important to fashion a Roux-limb of appropriate length to prevent this complication.